Human CLA+ Memory T Cell and Cytokines in Psoriasis - de Jesús-Gil, Carmen; Sans-de San Nicolàs, Lídia; García-Jiménez, Irene; Ferran, Marta; Pujol, Ramon M.; Santamaria-Babí, Luis F. (Frontiers in Medicine, 2021)
Psoriasis is a common inflammatory skin condition resulting from the interplay between epidermal keratinocytes and immunological cellular components, predominantly orchestrated by the IL-23/IL-17 axis. Among the circulating CD45R0+ memory T cells, those how belong to the regional cutaneous immune system are identified by the expression of the Cutaneous Lymphocyte-associated Antigen (CLA) on their surface. Because of their ability to recirculate between the skin and blood, circulating CLA+ memory T cells reflect the immune abnormalities found in different human cutaneous conditions, such as psoriasis. Based on this premise, studying the effect of different environmental microbial triggers (Streptococcus pyogenes and Candida albicans) and psoriatic lesional cytokines (IL-15 and IL-23) on CLA+ memory T cells, in the presence of autologous epidermal cells from patients, revealed greater IL-17F than IL-17A induction. Additionally, CLA+ T cells are a source of IL-9 in psoriatic patients, that is sustained over time similarly to IL-17A and IFN-γ, and enhanced S. pyogenes-induced IL-17A. Finally, different cytokine responses have been found in CLA+ memory T cells from plaque and guttate psoriasis patients, being related to different clinical parameters. All in all, the goal of this mini review is to present latest data regarding cytokines implicated in psoriasis immunopathogenesis from the prism of CLA+ memory T cells.